HIGHER ORDER THINKING SKILL (HOTS) IN ENGLISH LANGUAGE TEXTBOOK IN SENIOR HIGH SCHOOL - Dina Helmi Fitriani; Dhinuk Puspita Kirana (International Journal of Research on English Teaching and Applied Linguistics, 2022)
The level of reading comprehension questions in the textbook, particularly essay items, is thought to be important because previous research has shown that they can improve students' critical thinking skills in reading and help students learn English. The goal of this study was to look at the level of questions in an English course reading for high school seniors' reading comprehension questions. Anderson's taxonomy, which was used to analyze the level of reading comprehension questions, divides thinking skills into two categories: low order thinking skills (remembering, understanding, and applying) and high order thinking skills (remembering, understanding, and applying) (analyzing, evaluating, creating).The data were gathered and then calculated into percentages and frequencies that corresponded to each level of thinking within the questions. It appears that 77% of questions emphasize low-level questions, while 23% emphasize high-level questions (high order thinking skills). Furthermore, one of the low order thinking skills, comprehension, dominates the questions in the English reading material. As a result, the reading comprehension questions in the Bahasa Inggris English reading material for senior high school grade twelfth are generally classified as low level questions. As a result, teachers must devise questions that elicit students' higher order thinking skills.